Identifikasi Kebijakan Ketenagakerjaan pada Generasi Y dan Generasi Z Tentang Syarat Maksimal Usia Kerja di Indonesia - Asrifia Ridwan; HM Ismail (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2024)
The problem of difficulty in getting a job is very much felt by Gen Y and Z. They consider that one of the factors in the difficulty in getting a job is the existence of employment policies that provide opportunities for companies to set their own work provisions including the age requirements for applicants. The study aims to identify and analyze employment policies for generations Y and Z regarding the maximum working age requirements. This research method uses a type of library research with an agenda setting approach. The results of the study indicate that the identification of employment policies with provisions regarding the maximum working age requirements needs to be a government agenda to be fixed. This identification examines several factors. First, the initiation stage examines the existence of employment problems that were submitted to the Constitutional Court for a judicial review of the Manpower Law, Article 35 paragraph 1. Second, the diffusion stage identifies the need for a way out of the problem to eliminate the maximum working age requirements as has been done by the Philippines. Third, the processing stage responds that readiness to issue new policies requires a policy review that reviews; guarantees of the right to equal opportunity in work, changing the negative stigma of Gen Y and Z, providing multigenerational-based programs, and opening transparent employment opportunities.